“NEEDS NOT DEEDS”: The Scottish Children’s Hearing and the Enduring Legacy of Lord Kilbrandon - John Sturgeon; Elodie Leygue-Eurieult (Criminocorpus)
Due to political concerns about rising juvenile offending, the Scottish Office in Edinburgh established in 1961, a committee of enquiry to review systems and procedures for children appearing in Scottish Courts. The committee under judge Lord James Kilbrandon reported in 1964. Kilbrandon found that it was not possible to separate the underlying causes of children appearing in Court due to offending behaviour from those requiring care and protection. In both instances, he argued, the needs of the child had not been met by the adults responsible for their upbringing. Kilbrandon proposed a new system based on the needs of the child, the central role of the family in meeting the child’s needs, and the adoption of a preventative and educational approach to children in difficulty. The Scottish Children’s Hearing, a formally constituted legal tribunal but informal in its operation was created in law by the Social Work (Scotland) Act, 1968. Fifty years later it has stood the test of time and continues to operate in the way that Kilbrandon first envisaged it in 1964. In the words of Bottoms (2002,154), “the Children’s Hearing system is a relatively rare surviving example of a full-fledged, welfare-oriented system, and an assessment of its contemporary functioning is of great theoretical interest”. Kilbrandon’s legacy extends beyond the Children’s Hearing. His vision of shared community responsibility for the welfare of children and the lasting impact of adverse childhood events forms an essential element of Scottish public policy to children, to public health and to justice.